Taxation of Cryptocurrencies in Slovenia, Croatia, Bosnia and Herzegovina, and Serbia - Blažič, Anita (The Journal of Accounting and Management, 2025)
The article explores the legislative and tax rules for cryptocurrency taxation in Slovenia, Croatia, Bosnia and Herzegovina, and Serbia. Cryptocurrencies represent a new form of digital assets that, with their growing popularity and market value, attract the attention of legislators. Although cryptocurrencies are treated as a distinct form of digital assets in all the countries studied, the tax rules regarding trading and generating profits from cryptocurrencies vary significantly between them. Each of these countries takes a unique approach to taxing income derived from cryptocurrency trading or profit gained from the appreciation of digital currencies. In Slovenia, specific rules regarding the taxation of capital gains from cryptocurrencies are in place, while in Croatia, cryptocurrency profits are considered part of personal income tax. Serbia has introduced regulations that cover both mining and trading taxation, whereas in Bosnia and Herzegovina, the regulatory framework is still in its early stages. The article provides a comparative overview of the current legislation, highlighting differences in tax rates and tax obligations, and sheds light on the legal challenges faced by individuals and businesses in these countries.